Bond and flexural behaviour of a NSM CFRP strengthening system under fatigue loading - Fernandes, Pedro Miguel Gomes (2014)
The present paper aims to contribute to the knowledge of the long-term performance and durability of concrete structures strengthened with the Near-Surface Mounted (NSM) technique. The durability of strengthening systems is affected by environmental conditions, such as freeze-thaw and temperature cycling, exposure to aggressive chemical agents and ultraviolet light. Additionally, the long-term performance of the NSM system could be compromised by fatigue loading, which may result in deterioration and weakening of individual components (steel, FRP, concrete), or loss of bond performance and composite action. Thus, in order to assess the bond and flexural behavior of NSM CFRP strengthening system under fatigue loading, an experimental program was carried out, composing of direct pullout tests and loading of slab specimens. The main investigated parameters were the stress level (or fatigue stress) and the amplitude of cycle. This paper describes the conducted tests and presents and analysis the obtained results.